Role of Soviet Influence on Wedding Rituals: Reflections of Azerbaijani Cultural Practices - Jafarova, Jeyran (ADA University, 2023)
This study focuses on the role of religion as a cultural element, specifically investigating its influence on wedding rituals and its potential impact on cultural change by providing insight into the ensuing cultural transformation of Azerbaijan throughout the 20th century. The study aims to examine how religious practices within marriage ceremonies reflect cultural transformations throughout the Soviet period. The main discussion point is to find out the possible implications of the change in dominant cultural policy on lives of Azerbaijanis. To gain insights into historical shifts and the significance of religion, interviews were conducted with older generation women in Azerbaijan, allowing for a retrospective exploration of wedding practices through their experiences. Key concepts employed in this study include culture, cultural memory, cultural violence, intersectionality, and the cultural domain of power. The findings indicate that various regions exhibit distinct traditions in different stages of life, including wedding customs. The inhabitants of capital city were the ones mainly affected by the new cultural policies and regions of Azerbaijan could save their old traditions preserving the religious elements in it. Another finding was that family’s proximity to government (if they are serving for the ruling Communist Party) also had role in holding the traditional weddings. To explain, the ones working for the government had their weddings in Soviet style and avoided the religious elements in it. Findings show that, despite the introduction of atheistic ideologies and societal changes, religious practices and certain traditions continued to be observed privately.
Keywords: Wedding customs -- Azerbaijan; Religion and culture -- Azerbaijan; Cultural change -- Azerbaijan; Public and International Affairs